The agency effect: The impact of student agency on learning, emotions, and problem-solving behaviors in a game-based learning environment. (April 2020) - Taub, Michelle; Sawyer, Robert; Smith, Andy; Rowe, Jonathan; Azevedo, Roger; Lester, James
Abstract: Game-based learning environments are designed to foster high levels of student engagement and motivation during learning of complex topics. Game-based learning environments allow students freedom to navigate a space to interact with game elements that foster learning, i.e., agency. Agency has been studied in learning, and it has been demonstrated that increased student agency results in greater learning outcomes. However, it is unclear what is the level of agency that is required to demonstrate this effect, and whether this effect applies only to learning or to problem solving and affect during game-based learning as well. To investigate how the level of student agency impacts learning, problem solving, and affect, a study was conducted with 138 college students interacting with a game-based learning environment for microbiology, Crystal Island. This study is an extension of a previous study that examined the impact of agency on learning and problem-solving behaviors during game-based learning with Crystal Island. Students were randomly assigned to either a High Agency condition, a Low Agency condition, or a No Agency condition. It was found that students in the Low Agency condition achieved significantly higher normalized learning gain scores than students in the No Agency condition, and marginally higher normalized learning gains than the High Agency condition. Post-surveys of interest and presence indicated that students in the No Agency condition were less interested, and perceived themselves as less present in the virtual environment, than students in the other conditions. Students in the No Agency condition also experienced less frustration, confusion, and joy than the other agency conditions, indicating a less cognitively stimulating experience. Overall the results indicate that a moderate degree of agency provided to students in game-based learning environments leads to better learning outcomes without sacrificing interest and without yielding a negative emotional experience, demonstrating how even low levels of agency can positively impact learning, problem solving, and affect during game-based learning. Highlights: Examined the impact of agency (high, low, no) on learning with Crystal Island. The impact of agency on emotions, interest, and engagement was also examined. Students with low agency achieved the highest normalized learning gain scores. Students with no agency expressed the least confusion, frustration, or joy. Students with no agency reported the lowest levels of interest and engagement.